Effect of supplementation of Acacia honey and Pioglitazone on Lipid profile in streptozotocin induced diabetic rats - Khan, Mahvash; Arshad, Sidra; Aziz, Anbreen; Syed, Anjum; Shamsi, Nasar Abbas; Ayaz, Hira (Pakistan Journal of Physiology, 2020)
Background: There is growing interest in the use of alternative approaches like the use of herbs and natural products in the management of diabetes. The objective of this study was to determine the effect of combined supplementation of Pioglitazone and Acacia honey on lipid profile in streptozotocin induced diabetic rats. Methodology: This study was carried out on 150 male Sprague Dawley rats. The rats were divided into 5 groups with 30 rats in each group. Group I was normal control. Groups II–V, were given streptozotocin, intraperitoneally to make them diabetic. Group II was diabetic control. Group III was given acacia honey, group IV received intraperitoneal injection of pioglitazone (oral hypoglycaemic) along with Acacia honey, and group V was given pioglitazone intraperitoneally for same dose and duration. After 3 weeks of supplementation serum total cholesterol, low density lipoprotein, high density lipoprotein, very low density lipoprotein and triglycerides were measured. Statistical analysis was done on SPSS-20. All values were expressed as Mean±SEM. The differences were compared using one way analysis of variance followed by Tukey tests and p?0.05 were taken as significant. Results: After 3 weeks of supplementation serum triglycerides levels were significantly reduced in all groups while serum total cholesterol and low density lipoprotein levels were reduced in group IV only. Conclusion: Acacia honey along with Pioglitazone was able to improve lipid profile as indicated by decreased levels of total cholesterol, low density lipoproteins, and triglycerides in streptozotocin induced diabetic rats. Pak J Physiol 2019;15(4):3?6